The Effectiveness of Compassion-Focused Therapy on Resiliency, Self-discrepancy, Hope and Psychological Well-being of Menopausal Women in Ahvaz - Zhila Taher-Karami; Omid Hossieni; Zahra Dasht-Bozorgi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Menopause, or cession of menstruation, is a transition sign from fertility to infertility, during which women suffer from many physical and mental issues. The purpose of this study was to determine the effectiveness of compassion focused therapy on resiliency, self-discrepancy, hope and psychological well-being of menopausal women in Ahvaz. Materials and Methods: The research method was experimental, pretest-posttest with control group. Participants included 60 people who were selected by convenience sampling method: 30 participants in the experimental group and 30 in the control group were randomly assigned and the intervention was conducted for the experimental group The study instrument included Resiliency Questionnaire, Self-discrepancy Questionnaire, Hope Questionnaire, and Psychological Well-being Scale. Data were analyzed using one-way analysis of covariance (ANCOVA) by SPSS-22. Results: The mean (SD) age of women in the experimental group was 56.1 (3.3) and 55.7 (3.1) in the control group. The mean (SD) resiliency score in the pre-test of the experimental group was 47.7 (11.8), which increased to 55.8 (11.3) in the post-test, self-discrepancy decreased from 99.9 (12) to 85.6 (12.3), hope from 171.2 (19.7) to 189.7 (20.5) and psychological well-being increased from 34.9 (4.4) to 38.9 (4.5), but there was no significant change in the mean scores of the control group. Conclusion: Compassion-focused therapy improved resiliency, hope and psychological well-being and decreased self-discrepancy in postmenopausal women.